“Tjyvaparken” - The Thieves’ Park - An Osteological Study of Living Conditions and Structural Violence in 19th-Century Malmö - Ljungdahl,Izabelle (2025)
This thesis examines living conditions in Malmö during the 19th-century through the prevalence of stress related changes in an osteological material, in combination with historical archives. With a structural violence framework, the research aims to study health, nutrition, trauma and workload in individuals from the lowest socioeconomic group, soldiers and prisoners. An osteological analysis has been conducted on 23 individuals from Garnisonsplanteringen in Kirseberg, Malmö, where factors such as sex, age, stature and pathologies have been examined. Historical archives have been analysed where age, cause of death, time for imprisonment and sentence duration have been noted. The osteological analysis showed that the skeletal remains primarily had high frequencies of degenerative changes and poor dental health, which indicate poor living conditions and heavy physical labour. A summary of the archival records showed that tuberculosis, typhus, pneumonia, age and suicide were the leading causes of death, indicating overcrowding and bad living conditions, not only affecting the somatic health but also the mental health. Together, the osteological and historical data reveal that the individuals from Garnisonsplanteringen were marginalized and structurally vulnerable, and that their bodies carry the traces of lives shaped by social injustice and not personal choices.
Keywords: Garnisonsplanteringen; 19th-century; Malmö; soldiers; prisoners; structural violence; structural vulnerability; living conditions